Analysis Implementation of the Free Nutritious Meal Program (MBG) Policy in Indonesia (Edward III Implementation Model) - M. Rusdy Namsa (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
This study analyzes the implementation of the Free Nutritious Meal (MBG) program in Indonesia, a strategic national policy aimed at addressing stunting and malnutrition to support the "Indonesia Emas 2045" vision. Despite being launched as a political promise, the program faces critical public administration and operational challenges during its execution. These issues include a lack of comprehensive derivative regulations, weak local supervision, budget inefficiencies, and regional disparities in nutrition distribution, particularly in remote 3T (outermost, frontline, and disadvantaged) areas. Utilizing a systematic literature review (SLR) method, this study evaluates existing empirical research, policy modules, and scientific literature regarding school feeding initiatives. The results indicate that while the MBG program significantly improves students' nutritional status, cognitive abilities, and local economic growth through multiplier effects on MSMEs, its success is heavily constrained by bureaucratic bottlenecks and infrastructure unreadiness. Applying George C. Edwards III’s implementation model, the analysis reveals that policy success hinges on four critical variables: communication, resources, disposition, and bureaucratic structure. Therefore, this study recommends that the Indonesian government formulate detailed, localized Standard Operating Procedures (SOPs) and technical guidelines. Furthermore, it is essential to strengthen multi-sectoral coordination, enforce strict multi-stakeholder monitoring, and integrate local agricultural supply chains to ensure a transparent, accountable, and sustainable policy implementation across all regions.